A arrecadação do ICMS no Estado do Ceará - Fermanian, Carlos Alexandre Aguiar (2008)
Due to the growth of the tourism area and the searching for shore destinations with a important influence in economy, the State of Ceará is emphasized for its seeking due according to its comparative advantages and natural wealth. Among its main characteristics, the summer seazon is distinguished. Many are the reasons which brings a researcher to study the segment. It can be observed in this research that the seeking for the State of the Ceara as a destination grows proportionally. From econometrical regressions, the study analyzes the impact of the tourism in the collection of the ICMS from the State, analyzing unequals as the level of hotelkeeper occupation, tourist international demand and the tourist national demand. So this research desires to contribute in intention to make possible a directed publish-private politics to the tourist segment, believing faithfully in the natural capacity existent in the State of Ceará.